Economic policy and institutional change : a context-specific model for explaining the economic reforms failure in 1970's Colombia (2006)
ABSTARCT: This paper develops a context-specific model (Greif, 1997) to analyze the case of failed market-oriented reform in Colombia during 1974-78. The methodology keeps the contextual specificity at a manageable level, which is no more than the institutional structure under consideration, while it tries to maintain a parsimonious model. The theoretical framework is inscribed in the rational choice approach and game theory. This paper raises a standard question in economic reforms literature: why did the reforms fail? More comprehensively, what impeded progressive institutional change in this case? The answer is based on modelling theoretically and historically the strategic dilemmas brought about by the reforms and internacional shocks. Government appears here as an inflexible agenda setter poorly endowed; Coffee as the dominant player whose short-run interests won through, and Industry as the weak player who openly opposed to policies that the G-Cs coalition set out with the 1976 coffee boom. Ultimately the reforms failed because of Government‟s poor understanding of and limited autonomy for solving the dilemmas “economic reforms vs. coffee boom”, “Non-coffee sectors vs. Coffee sector”, and “Short-run vs. Long-run economic growth”.